The Interrelationship of Governance, Trust, and Ethics in Temporary Organizations. Issue 4 (August 2013) - Müller, Ralf; Andersen, Erling S.; Kvalnes, Øvind; Shao, Jingting; Sankaran, Shankar; Turner, J. Rodney; Biesenthal, Christopher; Walker, Derek; Gudergan, Siegfried
This study investigates the variety of ethical decisions of project managers and their impact from corporate governance and project governance structures. The roles of personal trust and system trust as a mechanism to steer ethical decision making in different governance settings is explored. Nine qualitative case studies in Europe, Asia, and Australia show that ethical decision making is contingent on trust, which in turn is contingent on the fulfillment of personal expectations within a given governance structure. The findings show the prerequisites for ethical decision making and the consequences of lack of trust. Further managerial and theoretical implications are discussed.